A simple procedure to assess the reliability of the best estimate thresholds (BETs): A case study on the detection threshold of tannic acid astringency - Martin, Christophe; Rollinat, Alix; Tournier, Carole; Peltier, Caroline (Food quality and preference, 2025)
•A simple method to identify subjects with potentially biased BETs was proposed.•The proposed method complements the ASTM procedure E679–04.•The method involves measuring the intensity of the different sample (3-AFC tests).•Potentially biased BETs were identified in a case study on astringency.•The average detection threshold for tannic acid astringency in water is 0.12 g/L.